2017
DOI: 10.1002/jat.3431
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of aniline and chlorinated anilines on zebrafish embryos and larvae

Abstract: Environmental risk assessments show increased attention to the sublethal effects of chemicals on aquatic organisms. The Organization for Economic Cooperation and Development (OECD) established the "Fish, Short-term Toxicity Test on Embryo and Sac-fry Stages" (OECD test 212) to predict lethal effects. It is still unclear, however, whether this test can predict sublethal effects. Although their sublethal effects are still unknown, chlorinated anilines are widely used in various fields. The purpose of this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Here we examined the lethal and sublethal effects of 20 common environmental chemicals in zebrafish embryos and larvae. A particularly steep increase in mortality after hatching was observed after exposure to 13 of the 20 test chemicals, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al ., ) or to chlorinated anilines (Horie et al ., ). Furthermore, Mu et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Here we examined the lethal and sublethal effects of 20 common environmental chemicals in zebrafish embryos and larvae. A particularly steep increase in mortality after hatching was observed after exposure to 13 of the 20 test chemicals, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al ., ) or to chlorinated anilines (Horie et al ., ). Furthermore, Mu et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we found that sublethal morphological abnormalities were induced by exposure to the test chemicals during the embryonic stage. We previously observed the morphological abnormalities edema and body curvature in zebrafish embryos exposed to one of several chlorinated anilines, as assessed by using OECD TG 212 (Horie et al ., ). In addition, in the present study, we found that exposure to each of the test chemicals induced absence of swim‐bladder inflation, which is consistent with previous reports (Li et al ., ; Villeneuve et al ., ; Horie et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, we previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, Iguchi, & Tatarazako, ; Horie, Yamagishi, Takahashi, et al, ), possibly because the chorion blocks the transport of certain chemical compounds (Kim & Tanguay, ; Olivares, Field, Simonich, Tanguay, & Sierra‐Alvarez, ). The results of the present study suggest that triclosan exposure negatively affects both the embryonic and the early larval stage in Japanese medaka, with a particularly steep increase in mortality soon after hatching, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al, ) or to chlorinated anilines (Horie, Yamagishi, Koshio, et al, ). Mu et al () and Yang et al () have also reported that the sensitivities of zebrafish to the acute toxic effects of environmental chemicals are different before and after hatching.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, toxicity testing using zebrafish embryos has been recommended from the point of view of animal welfare (EU, ). Ecotoxicological assays using zebrafish are increasingly used to clarify whether environmental chemicals induce abnormal embryogenesis because this effect is often induced at exposures lower than those are that cause lethal effects (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ). Indeed, there are reports that diclofenac induces abnormal embryogenesis in zebrafish (Chen et al, ; Horie, Yamagishi, Koshio, et al, ; Ribeiro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals,i.e., a particularly steep increase in mortality after hatching (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ), possibly because the chorion blocks the transport of certain chemical compounds into eggs (Kim & Tanguay, ; Olivares, Field, Simonich, Tanguay, & Sierra‐Alvarez, ). Morphological abnormalities at the embryo stage have been shown to be induced by various chemicals in zebrafish, and these abnormalities can lead to delayed development or mortality (Almond & Trombetta, ; Bonventre, White, & Cooper, ; Di Paolo et al, ; Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ; Melo et al, ; Mu et al, ; Vergauwen et al, ; Yang et al, ). This suggests that morphological abnormalities at the embryo stage may be suitable endpoints for predicting the lethal effects of environmental chemicals after hatching.…”
Section: Introductionmentioning
confidence: 99%